An Integrative Assessment of Self-Control, Deviant Friendships, and Fraudulent Behavior - Robinson-Smith, Tony (American journal of criminal justice, 2023)
Decades of research consistently support the link between poor self-control or deviant friendships with undesirable behavior. Rather than treating these theories as rival explanations, this study presents an assessment that explores a potential interconnection between self-control and social learning (differential association) in the prediction of deviant outcomes. Specifically, this investigation analyzes the mediating and moderating impact of deviant peer association upon the relationship between self-control and self-reported fraudulent behavior (academic dishonesty). Data gathered from an anonymous survey of undergraduate students (n = 490) generated findings that suggest deviant friendships mediate and moderate the association between self-control and fraudulent behavior. The implications of these findings are discussed.